Synthesis of starch nanocrystals with natural rubber derivatives in smart rubber for energy storage - Tan, Yi Wei (2025)
The ever-increasing human population has raised concerns about the need for environmentally friendly, sustainable and reliable energy storage system. Natural rubber (NR) is an elastomer which exhibits unique properties such as reversible deformation, excellent mechanical strength and large strain storage capacity rendering it as a promising prospect to be developed as a smart material with energy storage potential. However, a few drawbacks of NR for instance poor oil resistivity had raised the use of synthetic rubbers produced from petrochemicals that caused environmental and health issues. To counter this circumstance, the development of novel specialty natural rubber (SPNR) have been garnering tremendous interest due to the importance of green concept of rubber. However, the physical and mechanical characteristics of epoxidized natural rubber (ENR) and deproteinized natural rubber (DPNR) both belong to the class of SPNR fabricated in the form of rubber latex (RL) films are rarely investigated. This research work aims to analyse temperature-triggered biobased smart rubber with enhanced mechanical strength for energy storage application. More precisely, the emphasis of this research is to discover the compatibility of starch nanocrystals (SNC) as reinforcement nanofiller in NR and its derivatives such as ENR and DPNR for wide range of working temperatures. Moreover, the shape memory effect (SME) of SNC reinforced RL films is yet to be explored. Majority of the current research works related to smart materials are shape memory alloys and other electro-responsive material which are seldom 100% biodegradable and possessed less flexibility. From the engineering perspective, it is also crucial to analyse and demonstrate the feasibility of a novel material before any specific application. Therefore, the physical and mechanical characteristics, shape memory behaviour as well as evaluating the energy storage capability of the fabricated smart rubbers are presented in this research.